PERUSAHAAN SEBAGAI VARIABEL MEDIASI, DAN VISIBILITAS SEBAGAI VARIABEL MODERASI dalam HUBUNGAN ANTARA CSR dengan REPUTASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2016) - Nindya Humanitisri; Imam Ghozali (Diponegoro Journal of Accounting, 2018)
This study aims to examine the moderation effects of corporate visibility on the direct relationship between CSR with corporate reputation, and to examine the mediation effects of corporate reputation on the direct relationship between CSR with financial corporate performance. Independent variabel in this research is CSR. Mediation variabel in this research is corporate reputation. Moderation variabel in this research is corporate visibility. While the dependent variabel which used in this research is financial corporate performance.            This study uses secondary data from financial statements of companies that listed in Indonesia Stock Exchange and Bloomberg database. Sampling method that used is purposive sampling. The selected samples are manufactur companies from sector 3, 4, and 5 that publish about  CSR performance and have entertainment expense or promotion expense on their financial report years 2015-2016 in a row and available in Bloomberg. This study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method to examine the direct relationship between independent variable, mediation variable, moderation             Result of this study shows that CSR has positive effect on corporate reputation, corporate visibility has not moderation effect on the relationship between CSR and corporate reputation, and CSR has positive effect on the relationship between corporate financial performance by mediation effect of corporate reputation.